Service Quality Analysis to Increase Customer Satisfaction of Minimart Customers at Agricola Shophouse - Yen, Chow Kim Yen; Zheng Yu Xue (Yayasan Gema Bina Nusantara, 2023)
This study aims to find out how much the level of importance and satisfaction of service quality at minimarkets is measured through dimensions or indicators, namely the dimensions of tangible, reliability, responsiveness, guarantee, and attention. The population collected and used in this study were respondents who had chosen and used minimarkets. The method used in collecting data is a quantitative collection method using Google Forms as a media survey. The sampling technique used in this research is of the non-probability type. so that the total number of respondents collected in this survey was 30. Based on the importance performance analysis that we have done, it can be seen that in quadrant I there are 2 points that are important aspects of the research, namely product completeness (Q6) and employee knowledge (Q8), because they have a fairly small gap, namely -0.08 and 0.00. In quadrant II, there are several aspects that are good based on the research we have conducted, namely the ease of parking (Q1), the convenience of the payment system provided (Q4), the availability of employees to help consumers (Q9), and the layout of the product (Q10). Then, in quadrant III, there is one point, which is a low service aspect, namely regarding the price of the product offered (Q7). And finally, quadrant IV has several aspect points that have exceeded the limits of importance, namely free parking fees (Q2), employee friendliness (Q3), and speed of payment (Q5).